EFEKTIVITAS PENGGUNAAN MEDIA INTERAKTIF IFP DAN SMARTBOARD DALAM MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA SEKOLAH DASAR - Hikmah, Durratul; Afif, Sadad; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of Interactive Flat Panel (IFP) and smartboard as interactive media in improving IPAS learning outcomes of elementary school students, identify supporting factors for successful implementation, and describe their impact on student motivation and active engagement. The background of this study is the dominance of lecture methods in IPAS learning, resulting in low student motivation and many students failing to meet the Learning Objective Achievement Criteria (KKTP). This study employed a Narrative/Integrative Literature Review approach analyzing 10 SINTA-indexed national journal articles published in 2024-2026, obtained through systematic searches on Google Scholar, SINTA, and Garuda portal. Data were analyzed descriptively-analytically through three stages of the Miles and Huberman model, namely data reduction, data presentation, and synthesis. Findings consistently show that the use of IFP and smartboard significantly increases average scores and learning mastery across all reviewed studies. Both media also improve student motivation and active participation through visualizations of images, animations, videos, and touch screen features, making learning more active and meaningful. Implementation success is greatly influenced by teachers' TPACK competence in combining digital media with active learning models such as IBL and PBL.